1995
DOI: 10.1055/s-2006-957992
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Oriental Herbal Medicines on IL-8 Induction in Lipopolysaccharide-Activated Rat Macrophages

Abstract: Cytokine-induced neutrophil chemoattractant (CINC), a rat interleukin-8 (IL-8), was quantitated by using a sensitive ELISA. The CINC was induced up to 20 ng/ml from basal 1-2 ng/ml in lipopolysaccharide (LPS)-activated peritoneal macrophages. This CINC induction was significantly inhibited by steroidal anti-inflammatory drugs including dexamethasone, but not by non-steroidal drugs including indomethacin at all. Nine out of 59 herbal medicines which are frequently used in Korean traditional prescriptions for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 3 publications
1
44
0
Order By: Relevance
“…As well, HEDF revealed the presence of polysaccharides, which are ideal candidates for therapeutics with immunomodulatory and antitumor effects [33]. The result of this study was also in agreement with the reports that, plant phenolics and saponins (components of D. falcata [4]) are effective immunomodulators [3].…”
Section: Resultssupporting
confidence: 91%
“…As well, HEDF revealed the presence of polysaccharides, which are ideal candidates for therapeutics with immunomodulatory and antitumor effects [33]. The result of this study was also in agreement with the reports that, plant phenolics and saponins (components of D. falcata [4]) are effective immunomodulators [3].…”
Section: Resultssupporting
confidence: 91%
“…More than 50% inhibition of cytokine-induced neutrophil chemoattractant induction was shown to be exhibited by the dichloromethane fraction of Aralia continentalis with 0.05 mg/ml as a final concentration. 21) According to Hernandez et al,22) the extract of Aralia elata root revealed antiulcer and antisecretory characteristics. The structures of saponins, known to potent inhibitors of ethanol absorption, were determined by Yoshikawa et al 23) extracted from the bark and root of Aralia elata.…”
Section: Resultsmentioning
confidence: 99%
“…Saussurea costus is frequently used in Korean traditional prescriptions against inflammatory diseases. Its total MeOH extract at 0.1 mg/ml as a final concentration exhibited more than 50% of inhibition on the cytokine-induced neutrophil chemotactic (CINC) factor induction [212].…”
Section: Othersmentioning
confidence: 99%